Standardisation of in Vitro Techniques for mass Multiplication of Aranthera and Dendrobium - Sherly Kuriakose (Department of Horticulture, College of Agriculture, 1997)
Standardisation of in vitro techniques for mass multiplication of Aranthera and Dendrobium orchid varieties was attempted. The studies were carried out at the Plant Tissue Culture Laboratory, Department of Horticulture, College of Agriculture, Vellayani, during 1992-96. Attempts for the in vitro propagation via enhanced release of axillary buds, somatic organogenesis and somatic embryogenesis were made. One variety Annie Black of the monopodial orchid Aranthera and five varieties of the sympodial orchid Dendrobium were subjected to the initial response studies Sonia-17 (Dendrobium) and Annie Black (Aranthera) varieties were selected for detailed studies. Explants like shoot apices, leaf segments, root segments, keikis, inflorescence stalk were used. Mercuric chloride 0.1 per cent for ten minutes was identified as an effective surface sterilant. The lowest rate of microbial contamination was observed from January to May. The effect of culture medium (basal medium, mode of culture, strength of MS basal medium, major nutrient element, plant growth substances, casein hydrolysate, peptones, glutamine, sucrose, vitamins, yeast and malt extracts, fruit juices, coconut water, ethylene inhibitors) and culture conditions on in vitro shoot proliferation via enhanced release of axillary buds were studied.